1983
DOI: 10.1159/000234854
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immune Complexes and Their Possible Relevance to Other Immunological Parameters in Guatemalan Onchocerciasis

Abstract: Circulating immune complexes (CIC) were demonstrated in sera of Guatemalan patients with onchocerciasis by Raji cell radioimmunoassay. 44% of patients but none of controls had abnormally high concentrations of CIC in their sera. The increased concentrations of CIC were found more frequently in patients with lower density of microfilariae in their skin biopsies. Patients with higher concentrations of CIC appeared to have increased titers of serum antibodies to Onchocerca volvulus. A depression of both humoral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Concurrent O. volvulus infection has been shown to affect the immune response to tetanus (18,20,33), Mycobacterium bovis BCG (21,35), and yellow fever vaccines (5). The studies that have shown an impact of O. volvulus on tetanus seroconversion rates, however, have suffered from suboptimal immunization regimens (33) and excessively short (18,33) or noncomparable follow-up observations in infected and control subjects. Thus, the clinical relevance of these observations remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrent O. volvulus infection has been shown to affect the immune response to tetanus (18,20,33), Mycobacterium bovis BCG (21,35), and yellow fever vaccines (5). The studies that have shown an impact of O. volvulus on tetanus seroconversion rates, however, have suffered from suboptimal immunization regimens (33) and excessively short (18,33) or noncomparable follow-up observations in infected and control subjects. Thus, the clinical relevance of these observations remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Such a highly polarized immune environment might affect the immune response to nonparasite antigens. There is evidence from studies of experimental animal models (2,25,32) and humans (3,7,18,20,21,33,36) that chronic helminth infections may bias the cellular response to nonparasite antigens, leading to an inappropriate increase in Th2 cytokine production or a failure to produce the characteristic Th1 (IFN-␥) response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immune complexes have been detected in the serum of patients with onchocerciasis by a number of investigators using a range of methods (Lambert et al 1978, Paganelli, Ngu & Levinsky 1980, Steward et af. 1982, Greene et al 1983, Kawabata et al 1983; none of these studies were concerned with Onchocera t~olz~uIus specific complexes (OV-IC). It has been suggested that there is a positive correlation between the concentration of nonspecific circulating complexes (NS-IC) and the clinico-pathological features of onchocercal disease (Greene ef al.…”
Section: Introductionmentioning
confidence: 99%
“…1973; Grove and Frobes, 1979; Kawabata et al, 1983). In patients with Chagas' disease, caused by Trypanosoma cruzi, the previous reports on DTH to unrelated heterologous antigens remain controversial.…”
Section: Introductionmentioning
confidence: 99%